From Popular to Partisan Public Sphere: The Political Change of the Coffee Shops in Kepulauan Riau - Samnuzulsari, Tri; Edison, Edison; Yudiatmaja, Wayu Eko (Komunitas, 2019)
The primary aim of this study is to investigate the political transformation of the coffee shops in Kepulauan Riau before local leaders election. It is drived by the empirical facts that many coffee shops have transformed to be supporter of one of the candidates of local head government. By using grounded theory and thematic analysis, this study answers the critical questions of why the coffee shops change and what the factors affecting the transformation. A series of interview were conducted on a dozen of informants, consisted of political parties, campaign and success teams of the candidates, Local General Elections Commission (KPUD), Local Election Supervisory Agency (Bawaslu), the owners and the visitors of the coffee shop. Evidence of this study points out that the transformation of the coffee shops is the consequences of both political system and political structure in Indonesia. The empirical findings of this study are not only worthwile to the study of public sphere in the context of Indonesian local political setting but also to the practicioners in designing the truthful and fair local general election.Â Â